PENTINGNYA STRATEGI BISNIS DALAM MANAJEMEN HUBUNGAN PELANGGAN DALAM REVOLUSI INDUSTRI 4.0 - Muhammad Asrin Jazuli (AKUNTANSI 45, 2023)
This article aims to explain the importance of business strategy in customer relationship management in the industrial revolution 4.0. This paper uses a qualitative approach with the research method used is the analytical descriptive method. The data collection technique used in this research is literature study, which was carried out by reading books and literary journals about Business Strategy, Customer Relationship Management, and Industrial Revolution 4.0. This article is used to show the importance of business strategy in customer relationship management in the industrial revolution 4.0.